Synthetic gene network modeling, analysis, and robust design methods - Chen, Bor-Sen; Wang, Yu-Chao 1981- (CRC Press/Taylor & Francis Group, 2014)
This book develops a rational design and systematic approach to construct a gene network with desired behaviors. In order to achieve this goal, the registry of standard biological parts and experimental techniques are introduced at first. Then these biological components are characterized by a standard modeling method and collected in the component libraries, which can be efficiently reused in engineering synthetic gene networks. Based on the system theory, some design specifications are provided to engineer the synthetic gene networks to robustly track the desired trajectory by employing the component libraries.
Includes bibliographical references and index. - Print version record
Keywords: Gene regulatory networks; Genetic engineering; Genetics; genen; genes; netwerken; networks; wiskundige modellen; mathematical models; biologie; biology; modellen; models; ontwerp; design; methodologie; methodology; technologie; technology; Mathematical Models, Simulation Models; Biology (General); Wiskundige modellen, simulatiemodellen; Biologie (algemeen); Gene Regulatory Networks; Genes, Synthetic; Genetic Engineering; Models, Genetic; Réseaux de régulation génique; Génie génétique; Génétique; genetics; SCIENCE; Life Sciences; Genetics & Genomics